Student Project Management With Project-Based Learning: A Preliminary Study in The Polytechnic Malaysia - Sadrina Sadrina; Mohammad Mohd. Lassim; Muhammad Ichsan (PTE FTK UIN Ar-Raniry, 2015)
Finishing the project are the main task for last semester students in Polytechnic. They do the project in order finishing the syllabus without any improving skills for their future work in industry. The common educational system has improved the quantity of graduate but not the quality. Many industrial department dissatisfied with the workforce less of soft skills although they have enough hardskills in their field. Technical and vocational education has given an opportunity for students to develop their interested in technical and vocational program. Project Based Learning (PjBL) is one the various learning based on student oriented learning. Project-Based Learning is a student-centered learning approach based on the principles of constructivism to enhance students’ learning and creativity by solving a real-world problem. The purpose of this study was to asses the project management system by using Project-Based Learning. This study was held at Mechanical Engineering department at Polytechnic Kota Bharu, Malaysia. We used a set of questionnaire and observation into this research. We found Project-Based Learning are suitable for student project management. PjBL has improve students softskill such as communication skills, work in team, solving problem and creative. Futher application of this study will lead to the development of Project-Based Learning implement in other institution to improve student management project.